1983
DOI: 10.1128/aem.45.2.355-359.1983
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter jejuni in two California chicken processing plants

Abstract: Two federally inspected California chicken processing plants participated in Campylobacter jejuni prevalence studies. Twelve sampling sites were included in each of four groups. Groups were based on bird age, scald water temperature, and plant sampled. Scald water temperatures of 60 degrees C (140 degrees F) did not contribute to a lower prevalence of C. jejuni in edible parts, as did temperatures of 53 degrees C (127 degrees F) and 49 degrees C (120 degrees F). The feather picker and chilling tank were areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…Lammerding et al (1988) isolated C. jejuni from 74% of turkey meat samples and Acuff et al (1982) found campylobacters in 0-100% of turkey meat samples. Wempe et al (1989) proposed that the number of campylobacters in the intestine (10 6 g −1 in their study) correlated with the presence of the organism in the edible parts. Our study, which shows that the Campylobacter population in turkeys changes over time, indicates that the extent of carcass contamination could depend on when the birds are slaughtered.…”
Section: Discussionmentioning
confidence: 84%
“…Lammerding et al (1988) isolated C. jejuni from 74% of turkey meat samples and Acuff et al (1982) found campylobacters in 0-100% of turkey meat samples. Wempe et al (1989) proposed that the number of campylobacters in the intestine (10 6 g −1 in their study) correlated with the presence of the organism in the edible parts. Our study, which shows that the Campylobacter population in turkeys changes over time, indicates that the extent of carcass contamination could depend on when the birds are slaughtered.…”
Section: Discussionmentioning
confidence: 84%
“…On the farm, C. jejuni contaminates the environment once the chickens become colonized (Lindblom et al 1986;Gregory et al 1997). At the poultry processing plant, the organism has been isolated from a number of critical control points (Wempe et al 1983;Genigeorgis et al 1986). Previously, only a few attempts were made to isolate the organism from fomites that enter poultry farms during depopulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is almost impossible to prevent cross-contamination between different batches of chickens at the slaughter house regarding the usual slaughtering conditions. Scalding, mechanical evisceration and the subsequent washing and water chilling procedures favour the cross-contamination of carcasses (Wempe et al 1983;Cason et al 1999). This can lead to signi®cant rates of contamination, both in chickens and in processed products.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-contamination between different batches of chickens at the slaughterhouse is almost impossible to prevent with current slaughtering processes. Scalding, mechanical evisceration, washing and water chilling procedures tend to enhance cross-contamination of carcasses (Wempe et al 1983). This may explain the signi®cant rates of contaminated chicken products found in supermarkets.…”
Section: Introductionmentioning
confidence: 99%